Emotion in Group Decision and Negotiation - Martinovsky, Bilyana; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2015)
The volume offers an exploration of methods for analysis of emotion in negotiation, such as cognitive modeling, discourse analysis, all testing, subsequent multidimensional scaling, impression rating, and graph modeling for conflict resolution, reasonable and unreasonable disagreement. It covers activities, such as business negotiation, conflict solving, bargaining, task management meetings, discussions, and elaborates on different kinds of emotions. Some emotions stimulate negotiation (e.g. empathy), others -hinder it (e.g. disgust). However, all emotions open a door to uncertainty in relations and negotiation, which in turn provides an opportunity. The volume views language in negotiation not only as a vehicle for transmission of thought but also as a manifestation of emotion and the ethical. .
Introduction -- Chapter 1: Emotions in Interaction: Towards a Supraindividual Study of Empathy -- Chapter 2: With Feeling: How Emotions Shape Negotiation -- Chapter 3: The Cognitive-Affective Structure Of Political Ideologies -- Chapter 4: Reputation and Egotiation: The Impact of Self-Image on the Negotiator -- Chapters 5: Emotions in E-negotiations -- Chapter 6: Interaction Analysis of Emotion in Face-to-Face Group Decision and Negotiation -- Chapter 7: Emotion in Game Theory. .
Keywords: Psychology; Behavioral economics; Social sciences; Neuropsychology; Psychology; Neuropsychology; Behavioral/Experimental Economics; Social Sciences, general; Electronic books